Discovery New Drug Cycela barbata in Alcohol Use Disorder Using Pharmacological Methods - Febriyandi, Nuvandaru Fajar Dzikra; Jamil, Ahmad Shobrun; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2485, 2023)
Alcohol use disorder (AUD) is a medical condition characterized by an impaired ability to stop or control alcohol use including conditions that some refer to as alcohol abuse, alcohol dependence, alcohol addiction, and the colloquial term, alcoholism. The aim of this research is to find the potential of grass jelly ( Cyclea barbata ) for treating alcohol. The method used is in silico pharmacological network analysis. Secondary metabolite compound data was obtained from the Knapsack database, prediction of the ability to penetrate the blood brain barrier using the Boiled-Egg method in SwissADME. Prediction of proteins related to C. barbata used SwisstTargetPrediction. Pharmacological network analysis using StringDB and Disease Gene methods. The screening results from KnapSack showed 18 compounds, and only three compounds, namely beta-Cyclanoline, (-)-N-Methylcoclaurine, and (+)-Coclaurine, were predicted to be able to penetrate the blood-brain barrier using Boiled-EGG. From SwissTargetPrediction, 125 proteins related to C. barbata were obtained. From pharmacological network analysis, it was found that 6 proteins were related to alcohol use disorder, namely DRD3, HTR2A, SLC6A3, DRD2, OPRM1, and SLC6A4. So it can be concluded that C. barbata has potential as a plant that can be used to treat AUD.